Homozygous mutation of foxh1 arrests oogenesis causing infertility in female Nile tilapia. Issue 3 (14th December 2019) - Tao, Wenjing; Shi, Hongjuan; Yang, Jing; Diakite, Hamidou; Kocher, Thomas D; Wang, Deshou
Abstract: Foxh1, a member of fox gene family, was first characterized as a transcriptional partner in the formation of the Smad protein complex. Recent studies have shown foxh1 is highly expressed in the cytoplasm of oocytes in both tilapia and mouse. However, its function in oogenesis remains unexplored. In the present study, foxh1 −/− tilapia was created by CRISPR/Cas9. At 180 dah (days after hatching), the foxh1 −/− XX fish showed oogenesis arrest and a significantly lower GSI. The transition of oocytes from phase II to phase III and follicle cells from one to two layers was blocked, resulting in infertility of the mutant. Transcriptomic analysis revealed that expression of genes involved in estrogen synthesis and oocyte growth were altered in the foxh1 −/− ovaries. Loss of foxh1 resulted in significantly decreased Cyp19a1a and increased Cyp11b2 expression, consistent with significantly lower concentrations of serum estradiol-17β (E2) and higher concentrations of 11-ketotestosterone (11-KT). Moreover, administration of E2 rescued the phenotypes of foxh1 −/− XX fish, as indicated by the appearance of phase III and IV oocytes and absence of Cyp11b2 expression. Taken together, these results suggest that foxh1 functions in the oocytes to regulate oogenesis by promoting cyp19a1a expression, and therefore estrogen production. Disruption of foxh1 may block the estrogen synthesis and oocyte growth, leading to the arrest of oogenesis and thus infertility in tilapia.